Gambling problems among military personnel after deployment. (December 2020) - Cowlishaw, Sean; Metcalf, Olivia; Lawrence-Wood, Ellie; Little, Jonathon; Sbisa, Alyssa; Deans, Carolyn; O'Donnell, Meaghan; Sadler, Nicole; Van Hooff, Miranda; Crozier, Matilda; Battersby, Malcolm; Forbes, David; et al.
Abstract: Military and veteran populations may exhibit heightened vulnerability to gambling problems; however, there is scant relevant evidence outside the US, and few studies of transition periods, including return from operational deployment. The aim of this study was thus to highlight the extent, risk-factors, and implications of gambling problems among current members of the Australian Defence Force (ADF) following deployment to the Middle East Area of Operations (MEAO). It involved analyses of data from n = 1324 ADF personnel who deployed between 2010 and 2012, and completed surveys within four months of returning to Australia. The Problem Gambling Severity Index (PGSI) identified Problem Gambling (PG: PGSI ≥5) and At-Risk Gambling (ARG: PGSI 1–4), alongside measures of Depression (PHQ-9), Posttraumatic Stress Disorder (PCL-C), alcohol use problems (AUDIT), distress (K10), and post-deployment stressors. Analyses indicated that 7.7% of personnel reported at least some gambling problems post-deployment, including 2.0% that were distinguished by PG, and 5.7% indicating ARG. These figures were comparable to conditions including probable depression and alcohol dependence, while levels of any gambling problems were high relative to harmful drinking. Higher levels were observed among personnel who were aged 18–24, reported 0–4 years of military service, served in the Army, and comprised Non-Commissioned Officers/Other Ranks. There were strong associations with gambling problems and various indicators of mental health and wellbeing, and self-reported post-deployment difficulties. The findings indicate that gambling problems are salient concerns for some Australian military personnel post-deployment, and highlight the need for increased recognition and responses to these problems.